(untitled) (Al-Academy, 2015)
This research main goal is to identify the concept of relating and eliminating in visual arts and how does work as a philosophic and aesthetic concept of great importance in visual arts, specially in abstract field, for it is related to ornament (geometrical or botanical) for its rising is a sign for the operations of adding and deleting, and studying art products with such trend in their configuration and the boundaries of utilizing this concept. Then taking the art works of the artist Mahdi Mutashar as a research sample for procedural analysis. And outputs that tend in this direction in it’s formal being and know the limits of the concept of work -related dialectically interconnected. And then deal procedurally with the works of Iraqi painter Mehdi Mutashar , as the research sample , which we find to be clinging to his attempts of cultural Arab and Muslim origin become a clear sign that describe his artistic style. Therefore , the research tended to define the concept of deletion and addition in general and then its meaning and its applications in the Fine Arts through history , the resort then to dismantle the argument bilateral factors to its prominent leaders of the individual in accordance with what is happening in the works of Artist " Mutashar " and discuss the format reflective of what caused the deletion of the alterations to the second factor , while it becomes deletion sense added formality of the painting completed , and migrates portions deleted to a specimen optical Last become double added another approach for the growth of surface imaging in the light of the new relationship between the deleted additive origin and how to deal with it visually , so that adds quality in surface imaging , and is only artist with adding deleted , or resort to other cosmetic additions sings during the final structure of the proposed deal with the techniques or treatments chromaticity dimensions Avatar function , which is located within the incubator intellectual they handle. In light of this and go into correlation with the philosophical concept , we find that the artist " Mehdi Mutashar " strongly aware of the nature of visual Closed and clear understanding of the functioning of the concept of deletion and addition and how to employ in his visual.